SIFAT P-KONVEKS PADA RUANG FUNGSI MUSIELAK-ORLICZ TYPE BOCHNER - Yulia Romadiastri (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2013)
In this paper, we described about Musielak-Orlicz function spaces of Bochnertype. It has been obtained that Musielak-Orlicz function space L(;X) of Bochnertype becomes a Banach space. It is described also about P-convexity of Musielak-Orliczfunction space L(;X) of Bochner type. It is proved that the Musielak-Orlicz functionspace L(;X) of Bochner type is P-convex if and only if both spaces L and X areP-convex.